Relationship Between Family Acceptance And Support With Quality Of Life Of PWS (People With Schizopherenia) At The Polyclicnic Of Jambi Province Hospital - Anipah, Anipah; Erwinsyah, Erwinsyah; Rosdawati, Rosdawati; Dormina, Dormina (Jurnal Ilmu-Ilmu Kesehatan, 2025)
Background: The quality of life of people with schizoprenia (ODS) impacts an individual's physical health, mental health, level of dependence, trust as well as relationship with the surrounding environment. Factors affecting ODS quality of life are poor family acceptance of ODS and low family support. This study aims to determine the relationship between acceptance and family support with the quality of life of ODS. This type of research is a correlation study with a cross-sectional study approach. Res criteria. The criteria for respondents were families who lived with ODS, cared for and carried ODS controls, were 20 years old and over, and could read and write. Respondents were taken using purposive sampling techniques. A total of 329 ODS families have contributed and completed all stages of this research. The variables in this study were quality of life as measured by the Schizophrenia Quality Of Life Scale (SQOLS), family acceptance and family support variables. Research data analyzed using person product moment correlation test and multiple linear regression test. The results found that there was a significant relationship between family acceptance with ODS quality of life (p-value = 0.000), and family support with ODS quality of life (p-value = 0.000). The factor most associated with quality of life was family support (1,319). It is expected that the involvement of health services and families in caring for ODS to improve the quality of life of ODS so that Can improve family coping strategies as a support system in overcoming health problems.